USING GO FASTER TECHNIQUE TO IMPROVE THE HORTATORY EXPOSITION TEXT READING SKILL OF THE ELEVENTH GRADERS OF SMA NEGERI 3 MAGELANG IN SCHOOL YEAR 2017/2018 - pri - yanti (Faculty of Education and Teachers Training, 2018)
ABSTRACTReading is one of the four language skills that should be mastered well be senior high school students in learning English, one of them is reading skill. This language skill, unfortunately, has not been well mastered by the eleventh graders of SMA N 3 Magelang. Mostly, the students find some difficulties in practising English reading activity. It becomes worse because of their low motivation in learning English. The fact shows that the students’ average score in reading skill is 68. It means that their average score was less than standard minimum score of passing grade which is 77. There are some factors that cause this condition. One of the factors is the monotonous way of teaching that makes the students have low motivation to study English reading. There are two objectives of this research. They are to know whether the use of Go Faster technique can increase the leraning motivation of the eleventh graders of SMA Negeri 3 Magelang in reading of hortatory exposition text and to know how great the improvement of the students reading skill on hortatory exposition text who are taught using Go Faster technique. The writer took the eleventh graders of SMA N 3 Magelang as the subject of the research. The writer conducted a Classroom Action Research (CAR). It was divided into three phases, Pre-Cycle, Cycle I, Cycle II. The techniques used to collect the data were test and non-test techniques. The writer used score percentage in each cycle to analyze the data.The result of the test shows that the percentage of the students who got the score of 77 or above increased 12,27 point after they were taught using Go Faster Technique. In the Pre-Cycle, the students’ average score was 71,56 and after they were taught using Go Faster Technique in Cycle I, the score was 76.30. The average score in Cycle II was 83.83 and it means there was improvement 7.53 point from Cycle I. Then, there was also a positive change of the students’ motivation to learn English. They were enthusiastic to improve their skill in reading a hortatory exposition text.Based on the result above, the writer concludes that Go Faster Technique is one of the good technique of teaching reading especially reading a hortatory exposition text which are applied in senior high schools. This technique can improve the students’ motivation and their hortatory exposition reading skill. The writer recommends English teachers to use Go Faster Technique as an alternative way of teaching reading to senior high school students.